2019
DOI: 10.1186/s12935-019-1005-9
|View full text |Cite
|
Sign up to set email alerts
|

The influence of PFK-II overexpression on neuroblastoma patients’ survival may be dependent on the particular isoenzyme expressed, PFKFB3 or PFKFB4

Abstract: Background/AimDuring cancer progression metabolic reprogramming is observed in parallel to the alternation in transcriptional profiles of malignant cells. Recent studies suggest that metabolic isoenzymes of phosphofructokinase II (PFK-II) – PFKFB3 and PFKFB4, often induced in hypoxic environment, significantly contribute to enhancement of glucose metabolism and in consequence cancer progression.Materials and methodsUsing the publicly available data deposited in the R2 data base we performed a Kaplan–Meyer anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The role of enhanced glucose breakdown in carcinogenesis is well known because the attenuation of glycolysis inhibits the growth, and decreases the survival, of cancer cells. High PFKFB3/4 expression is signi cantly correlated with shorter overall survival in several cancers, such as cervical squamous cell carcinoma, colon cancer, glioma, melanoma, and neuroblastoma [28]. In a previous study, a high amount of PFKFB4 was found to indicate a poor prognosis in breast cancer because it is related to increased rates of metastasis [29].…”
Section: Discussionmentioning
confidence: 97%
“…The role of enhanced glucose breakdown in carcinogenesis is well known because the attenuation of glycolysis inhibits the growth, and decreases the survival, of cancer cells. High PFKFB3/4 expression is signi cantly correlated with shorter overall survival in several cancers, such as cervical squamous cell carcinoma, colon cancer, glioma, melanoma, and neuroblastoma [28]. In a previous study, a high amount of PFKFB4 was found to indicate a poor prognosis in breast cancer because it is related to increased rates of metastasis [29].…”
Section: Discussionmentioning
confidence: 97%
“…In brain tumors, including high-grade gliomas, PFKFB3 expression has been linked to poor survival [ 127 , 128 , 129 , 130 ]. However, targeted PFKFB3 inhibition may provide a therapeutic option for CNS tumor patients.…”
Section: Discussionmentioning
confidence: 99%
“…As such, efficacious delivery of chemotherapy is difficult with chemoresistance developing in most malignant CNS tumor patients. High PFKFB3 LOH at 10p14-p15, as well as low UBI2K4 expression levels in glioblastoma, has been shown to portend a poor prognosis with an overall poor survival [ 127 , 128 , 129 , 130 ].…”
Section: Pfkfb3 In Central Nervous System Tumorsmentioning
confidence: 99%
See 2 more Smart Citations